Porous spherical silica, catalyst carrier, cosmetic, analysis column, polishing agent, resin composition, and method for producing porous spherical silica
The manufacturing process of gelling and calcining fumed silica dispersion produces spherical silica with high hardness and controlled particle size, addressing durability and shape issues, enhancing its use in catalyst carriers, analytical columns, and abrasives, and providing a smooth feel as a cosmetic additive.
Patent Information
- Application Number
- JP2024195469
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-06
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2044-02-29
AI Technical Summary
Porous silica materials face issues with disintegration due to their porous structure, leading to durability problems in long-term catalyst carriers and analytical column packing agents, and particle shape distortion during resin kneading in abrasives, along with challenges in maintaining the porous structure during high-temperature calcination.
A manufacturing process involving gelling a fumed silica dispersion in a liquid, followed by spray drying and calcination at specific temperatures, reduces alkali metal content and enhances particle hardness, resulting in spherical silica with controlled particle size distribution, high pore volume, and reduced fragmentary particles.
The process produces porous spherical silica with high hardness and maintained structure, suitable for long-term use in catalyst carriers and analytical columns, and improved handling in abrasives, while minimizing particle blockage and providing a smooth feel as a cosmetic additive.
Smart Images

Figure 2025019080000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel porous spherical silica, a catalyst support, a cosmetic, an analytical column, an abrasive, a resin composition, and a method for producing porous spherical silica. [Background technology]
[0002] Porous silica has been studied in various ways, and porous silica with various physical properties has been proposed. Porous silica can be produced, for example, by a method of neutralizing an aqueous solution of an alkali metal silicate by adding a mineral acid, and separating and collecting the resulting particles (Patent Document 1), a method of spray-drying a fumed silica dispersion (Patent Document 2), or a method of gelling a fumed silica dispersion in a liquid (Patent Document 3). The porous silica produced by the above methods has characteristics in pore volume and pore size, and is expected to be used as a catalyst carrier or a packing material for an analytical column. Furthermore, when used as an abrasive for industrial products, etc., the resin penetrates into the pores, making it easy to fix the resin on the polishing pad. The use of spherical products for the above applications has the advantage of making it easy to adjust the particle size and improve the packing rate. In addition, porous spherical silica has a smooth feel due to its shape, so it is also useful as a cosmetic additive. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2004 / 101139 Brochure [Patent Document 2] International Publication No. 2019 / 131873 Brochure [Patent Document 3] International Publication No. 2022 / 154014 Brochure [Non-patent literature]
[0004] [Non-Patent Document 1] "Sintering of Fine Ceramics", Journal of the Society of Powder Technology, Vol. 25, No. 12, (1988), pp. 805-811 Summary of the Invention [Problem to be solved by the invention]
[0005] However, since porous silica has a tendency to easily collapse due to its porous structure, it has a problem with durability when used as a catalyst carrier used for a long period of time or as a packing material for an analytical column used in a fluid. In addition, when used as an abrasive for industrial products, etc., there is a problem that the particle shape is distorted or broken during the kneading process with resin, which deteriorates the handling properties. Generally, a calcination method is used to increase the hardness of inorganic materials (Non-Patent Document 1), but in the porous silica described in Patent Document 1, which uses sodium silicate as a raw material, the pores are blocked by calcination at high temperatures due to the melting point drop caused by the inclusion of sodium derived from the raw material, and the porous structure cannot be maintained.
[0006] The porous silica described in Patent Document 2, which is obtained by spray drying a fumed silica dispersion, has a low compressive strength after firing, and it is not possible to obtain silica with high hardness. The porous silica described in Patent Document 3, which is obtained by gelling a fumed silica dispersion in a liquid, causes particles to aggregate upon firing, requiring a crushing process, but this process generates fine fragments, which reduces the circularity of the particles as a whole. When the porous spherical silica is used as a packing material for an analytical column, the inclusion of the fine powder causes column blockage, and when the porous spherical silica is used as a cosmetic additive, it deteriorates the feel.
[0007] Therefore, an object of the present invention is to provide porous spherical silica having independent spheres with a reduced alkali metal content, high particle hardness, and a reduced number of fragmentary particles, and a method for producing the same. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that in the process of producing porous spherical silica, a gel obtained by gelling a fumed silica dispersion in a liquid is spray-dried and then fired, thereby producing porous spherical silica having a reduced alkali metal content, high particle hardness, and a reduced number of fragmentary particles, which has independent spheres. This has led to the completion of the present invention.
[0009] [1] The volume-based cumulative 50% diameter (D50) measured by the Coulter counter method is in the range of 2 μm to 200 μm, Similarly, the ratio (D10 / D90) of the cumulative 10% diameter (D10) to the cumulative 90% diameter (D90) is 0.3 or more, The pore volume according to the BJH method is 0.5 ml / g or more and 8 ml / g or less, The most frequent value of the pore radius according to the BJH method is 5 nm or more and 50 nm or less, The specific surface area according to the BET method is 50m 2 / g or more, 400m 2 / g or less, According to the method specified in JIS Z8844, the arithmetic mean value of the "test force at which the specimen breaks" for 10 particles, calculated at a loading speed of 0.4462 mN / sec, is 1.0 x 10 1 mN or more 2.0×10 1 mN or less, For every 200 particles observed in an SEM image, there are 20 or fewer particles with a circularity of 0.7 or less; 1. Porous spherical silica having an alkali metal content of 50 ppm or less.
[0010] [2] A catalyst carrier comprising the porous spherical silica described in [1]. [3] A cosmetic comprising the porous spherical silica described in [1]. [4] An analytical column comprising the porous spherical silica described in [1].
[0011] [5] An abrasive comprising the porous spherical silica described in [1]. [6] A resin composition comprising the porous spherical silica described in [1].
[0012] [7] A process for preparing a W / O emulsion comprising an aqueous phase having fumed silica dispersed therein and an organic phase mainly composed of a non-aqueous solvent; a step of heating the emulsion to gel the aqueous phase and obtain a gelled dispersion; A step of recovering the resulting gel from the liquid and spray drying it; and and calcining the obtained porous spherical silica at a temperature of 900 to 1500°C for 10 to 25 hours. [8] The method for producing porous spherical silica according to [7], characterized in that the spray method for spray drying is a two-fluid nozzle method. Effect of the Invention
[0013] The porous spherical silica of the present invention has a high pore volume and a high hardness, as shown by the high "test force when the destruction of the sample is observed", so that even when used for a long period of time or in a fluid, the porous structure can be maintained without particle collapse or pore blockage. Therefore, by using the porous spherical silica of the present invention, the durability required for catalyst carriers, adsorbents for carbon dioxide, etc., and analytical column packings can be improved. Furthermore, when used as an abrasive for industrial products, etc., the particle strength is strong enough to withstand kneading with resin, and the handling properties in the manufacturing process are improved.
[0014] In addition, as shown by the high D10 / D90 ratio, the particle size distribution is narrow, so when used as a packing material for an analytical column, clogging due to fine powder entering the gaps between particles is unlikely to occur.
[0015] Furthermore, out of 200 particles observed in SEM images, there were 20 or fewer particles with a circularity of 0.7 or less, reducing the number of fragmentary particles, and the particles are independent spherical, so that when used as a cosmetics additive, it can impart a smooth feel to the skin. Furthermore, the purity is high, with an alkali metal content of 50 ppm or less, and it is extremely useful as an abrasive for semiconductors and other devices that should not contain alkali metals.
[0016] In the manufacturing method of the present invention, the raw material is spray-dried and then calcined to suppress the aggregation of particles, which makes it possible to manufacture the porous spherical silica without a crushing step. This makes it possible to suppress the generation of fragmented particles that would occur if a crushing step were carried out, and makes it possible to manufacture the porous spherical silica having the above characteristics without generating fine powder or decreasing the circularity of the particles as a whole.
[0017] Furthermore, in the manufacturing method of the present invention, the strength of the bonds between the primary particles is improved by calcining under specific conditions, which makes it possible to obtain porous spherical silica with high particle hardness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The following embodiments are merely examples of the present invention, and the present invention is not limited to these embodiments.
[0019] <Porous spherical silica> The porous spherical silica of the present invention has a volume-based cumulative 50% diameter (D50) in the particle size distribution measured by the Coulter counter method in the range of 2 μm to 200 μm, and the ratio (D10 / D90) of the cumulative 10% diameter (D10) to the cumulative 90% diameter (D90) is 0.3 or more. If the porous spherical silica is in the above range, when it is used as a packing material for an analytical column, the column is less likely to be clogged and is easy to pack. D50 is preferably 2 μm to 100 μm, particularly preferably 5 μm to 50 μm, and more preferably 5 μm to 20 μm. D10 / D90 is preferably 0.4 or more, and more preferably 0.5 or more. D10 / D90 cannot exceed 1.0, and is generally 0.6 or less.
[0020] The porous spherical silica of the present invention has a pore volume of 0.5 ml / g or more and 8 ml / g or less, as measured by the BJH method described below. It is difficult to obtain a pore volume larger than 8 ml / g. If it is 6 ml / g or less, it is easier to produce, if it is 4 ml / g or less, it is even easier to produce, and if it is 2.5 ml / g or less, it is particularly easy to produce. In particular, when the porous spherical silica of the present invention is used as a catalyst carrier or an adsorbent for carbon dioxide or the like, in order to have a high loading amount or adsorption amount, the pore volume is preferably 0.6 ml / g or more, more preferably 0.7 ml / g or more, and even more preferably 1.0 ml / g or more.
[0021] The mode of the pore radius according to the BJH method is 5 nm or more, preferably 10 nm or more, and more preferably 15 nm or more, and the upper limit is 50 nm or less, and preferably 30 nm or less.
[0022] The pore volume and pore radius measured by the BJH method were obtained by drying the sample to be measured at 200°C for 3 hours or more under a vacuum of 1 kPa or less, obtaining an adsorption isotherm only on the nitrogen adsorption side at liquid nitrogen temperature, and analyzing it by the BJH method (Barrett, EP; Joyner, LG; Halenda, PP, J. Am. Chem. Soc. 73, 373 (1951). "The most frequent value of pore radius measured by the BJH method" means the value of the pore radius at which the pore distribution curve (volume distribution curve), obtained by analysis by the BJH method and plotting the derivative of the cumulative pore volume with respect to the logarithm of the pore radius on the ordinate and the pore radius on the abscissa, takes the maximum value.
[0023] The porous spherical silica of the present invention has a specific surface area of 50 m2 by the BET method. 2 / g or more, 400m 2 / g or less. The specific surface area is preferably 100 m 2 / g or more, 120m 2 / g or more, 350m 2It is particularly preferable that the specific surface area of the porous spherical silica is in the range of 400 m2 or less. The higher the specific surface area of the fumed silica used as the raw material, the higher the specific surface area of the porous spherical silica. Also, the higher the specific surface area of the fumed silica, the easier it is to gel and the easier it is to mold it into a sphere. Generally, the specific surface area of fumed silica is 400 m2 or less. 2 / g or less, so the specific surface area is 400m 2 It is difficult to obtain porous spherical silica having a specific surface area exceeding this value. Note that the specific surface area is a value measured by the nitrogen adsorption BET multipoint method.
[0024] The porous spherical silica of the present invention has an arithmetic mean value of the "test force at which the specimen was broken" (hereinafter referred to as the "test force at break") for 10 particles, determined at a loading rate of 0.4462 mN / sec according to the method specified in JIS Z8844:2019, of 1.0 x 10 1 ~2.0×10 1 The test force at break is 2.0×10 1 If the molecular weight exceeds 1.0×10 mN, it becomes difficult to obtain porous spherical silica having a pore volume of 0.5 ml / g or more. 1 ~1.8×10 1 If the test force at the time of breaking is within the above range, the particles have high hardness and become porous spherical silica having the desired durability.
[0025] The porous spherical silica of the present invention has an alkali metal content of 50 ppm or less (by mass), preferably 40 ppm or less, and more preferably 30 ppm or less.
[0026] The porous spherical silica of the present invention has a spherical shape. Here, spherical means that the average circularity determined by image analysis using a scanning electron microscope (SEM) is 0.8 or more. The "average circularity determined by image analysis" is the arithmetic mean value of the circularity obtained by image analysis of SEM images observed at a magnification of 1000 times with an SEM for 2000 or more porous spherical silica particles. Here, the "circularity" is a value calculated by the following formula (1).
[0027] C=4πS / L 2 (1) In the above formula (1), C represents the circularity, S represents the area (projected area) that the porous spherical silica occupies in the image, and L represents the length (perimeter) of the outer periphery of the porous spherical silica in the image. The average circularity is particularly preferably 0.85 or more.
[0028] The porous spherical silica of the present invention has a number of shard particles of 20 or less out of 200 particles observed in an SEM image. Here, shard particles refer to particles having a circularity of 0.7 or less as calculated according to the above definition. The number of shard particles is preferably 15 or less, more preferably 10 or less.
[0029] The porous spherical silica of the present invention may be hydrophilic or hydrophobic. The porous spherical silica of the present invention produced by the production method described below is hydrophilic. Hydrophobic porous spherical silica can be obtained by appropriately applying a silica surface treatment method after obtaining hydrophilic porous spherical silica by the production method. Here, "hydrophilic" means that it can be dispersed in water that does not contain an organic solvent.
[0030] Since the porous spherical silica of the present invention has the above-mentioned properties, it can be used as a carrier for catalysts or fragrances, an adsorbent for carbon dioxide and the like, a filler for analytical columns, an additive for cosmetics, an abrasive for industrial products and the like, and an additive for various resin compositions.
[0031] <Method for producing porous spherical silica> The method for producing the porous spherical silica of the present invention is not particularly limited, but the high pore volume and the most frequent diameter of the pore radius can be easily achieved by using fumed silica dispersion as raw material.In general, fumed silica has a structure in which fine particle silica (primary particles) are aggregated.Therefore, by using fumed silica dispersion as the raw material for porous spherical silica, and gelling the fumed silica in the dispersion to form a network, the decrease in pore volume caused by drying shrinkage can be suppressed, and it is possible to obtain porous spherical silica with high pore volume.
[0032] More specifically, a method for producing porous spherical silica includes preparing a W / O emulsion consisting of an aqueous phase in which fumed silica is dispersed and an organic phase mainly composed of a non-aqueous solvent (W / O emulsion preparation step), then heating the emulsion to gel the aqueous phase to obtain a porous spherical silica dispersion (gelation step), recovering the resulting porous spherical silica from the liquid (gelation recovery step), spray drying (drying step), and calcining (calcination step). Each step will be described in detail below.
[0033] (W / O emulsion preparation process) As a method for preparing a W / O emulsion consisting of an aqueous phase in which fumed silica is dispersed and an organic phase mainly composed of a non-aqueous solvent, it is particularly preferable to adopt a method in which a dispersion in which fumed silica is dispersed in an aqueous phase is first prepared (dispersion preparation step), and then an emulsion is prepared by a standard method using this and an organic solvent (emulsification step). These will be further explained below.
[0034] (Dispersion liquid preparation process) The dispersion preparation step is a step of dispersing fumed silica in water to prepare a dispersion.
[0035] The fumed silica used is dispersible in water and can be gelled by heating, adjusting the pH, etc. Such properties are achieved by having a large number of silanol groups on the silica surface, so almost any fumed silica that has not been surface-treated can be used. In addition, due to the ease with which gelling can proceed, the specific surface area of the fumed silica is set to 100 m 2 / g or more, especially 200m 2 It is preferable to use a material having a molecular weight of 250m / g or more. 2 / g or more is more preferable. The larger the specific surface area, the faster the gelation proceeds, and the easier it is to gel the droplets (W phase) in which the fumed silica is dispersed. From the viewpoint of ease of availability, the upper limit is 400 m 2 It is preferable to use one having a specific surface area of 100 / g. The specific surface area is a value measured by a nitrogen adsorption BET multipoint method.
[0036] The specific surface area of the porous spherical silica obtained by the method described here increases as the specific surface area of the fumed silica used as raw material increases.Therefore, by appropriately selecting the fumed silica used as raw material according to the specific surface area of the targeted porous spherical silica, the specific surface area of the porous spherical silica can be arbitrarily controlled without changing the manufacturing conditions.In addition, the fumed silica used in the present invention can be mixed with those having different specific surface areas.
[0037] The above-mentioned fumed silica is commercially available, and for example, various hydrophilic grades of Reolosil from Tokuyama Corporation, various hydrophilic grades of Aerosil from Nippon Aerosil Co., Ltd., and various hydrophilic grades of dry silica HDK from Wacker Asahi Kasei Silicone Co., Ltd. can be used.
[0038] Furthermore, since fumed silica is generally highly pure and contains almost no impurities such as alkali metals, the alkali metal content of the produced porous spherical silica can be made extremely small.
[0039] Water is essential as the solvent in this step, but other solvents may be included as long as they do not inhibit the formation of the emulsion or the subsequent gelation. In addition, when a latent base is used to promote the gelation described below, it is advisable to dissolve the base in water before dispersing the fumed silica.
[0040] A preferred method for dispersing fumed silica in a solvent is to prepare a dispersion in which fumed silica is preliminarily dispersed in a solvent, and then finely disperse the dispersion using a crusher or the like. Specific examples of crushers that can be used for finely dispersing include ball mills, bead mills, vibration mills, pin mills, atomizers, colloid mills, homogenizers, high-pressure homogenizers, and ultrasonic homogenizers. As for the degree of dispersion after fine dispersion, it is preferred that the D90 value is 0.5 μm or less when the particle size distribution of the dispersion is measured by a laser diffraction scattering method.
[0041] The silica concentration in the fumed silica dispersion is preferably in the range of 10% by mass to 30% by mass. It is more preferably 15% by mass or more, and particularly preferably 20% by mass or more. The higher the silica concentration in the fumed silica dispersion, the faster the gelation proceeds, but if the silica concentration is too high, it loses fluidity and it becomes difficult to obtain a fumed silica dispersion.
[0042] The gelation of the fumed silica dispersion is accelerated by heating. If the gelation of the fumed silica dispersion progresses during the dispersion preparation step, the W phase will be difficult to form a sphere in the next emulsification step, and in extreme cases, the emulsion molding itself will be difficult. Therefore, in the dispersion preparation step, it is preferable to keep the liquid temperature of the fumed silica dispersion at about room temperature (20°C) or lower. When the specific surface area or concentration of the fumed silica is high and gelation is likely to progress, it is also effective to cool it to a temperature lower than room temperature (preferably 15°C or lower, more preferably 12°C or lower).
[0043] (Emulsion process) The W / O emulsion preparation step is a step of dispersing the fumed silica dispersion obtained in the dispersion preparation step in a non-aqueous solvent to form a W / O emulsion. By forming such a W / O emulsion, the fumed silica dispersion, which is a dispersoid, becomes spherical due to surface tension, etc., and a spherical gelled body can be obtained by gelling the fumed silica dispersion dispersed in the non-aqueous solvent in the spherical shape.
[0044] The non-aqueous solvent used in the present manufacturing method may be a solvent having a hydrophobicity to such an extent that it can form an emulsion with the fumed silica dispersion. For example, organic solvents such as hydrocarbons and halogenated hydrocarbons can be used as such solvents. More specifically, non-aqueous solvents such as hexane, heptane, octane, nonane, decane, liquid paraffin, dichloromethane, chloroform, carbon tetrachloride, and dichloropropane can be used. Among these, hexane, heptane, and decane, which have a suitable viscosity, can be preferably used. If necessary, a plurality of solvents may be mixed and used. In addition, it is also possible to use a hydrophilic solvent such as a lower alcohol in combination (as a mixed solvent) as long as it can form an emulsion with the fumed silica dispersion.
[0045] The amount of the non-water-soluble solvent used is not particularly limited as long as it is within a range that allows the formation of a W / O emulsion, but generally, the non-water-soluble solvent is used in an amount of about 1 to 10 parts by volume per part by volume of the fumed silica dispersion.
[0046] In the present production method, it is preferable to add a surfactant when forming the W / O emulsion. As the surfactant to be used, any known surfactant used in forming a W / O emulsion can be used without any restrictions, and any of anionic surfactants, cationic surfactants, and nonionic surfactants can be used. Among these, nonionic surfactants are preferred because they are easy to form a W / O emulsion and are less likely to be contaminated with alkali metals. In particular, surfactants having an HLB value of 3 or more and 5 or less, which is a value indicating the degree of hydrophilicity and hydrophobicity of a surfactant, can be preferably used. Here, the "HLB value" means the HLB value according to the Griffin method. Specific examples of surfactants that can be preferably used include sorbitan monooleate, sorbitan monostearate, and sorbitan monosesquioleate.
[0047] The amount of the surfactant used is the same as that generally used when forming a W / O emulsion. Specifically, the amount of the surfactant used is preferably in the range of 0.05 g to 10 g per 100 ml of the fumed silica dispersion.
[0048] When forming a W / O emulsion, a known method for forming a W / O emulsion can be adopted as a method for dispersing the fumed silica dispersion in a non-aqueous solvent. From the viewpoint of ease of industrial production, the emulsion is preferably formed by mechanical emulsification, and specifically, a method using a mixer, homogenizer, etc. can be exemplified. A homogenizer can be preferably used. Since an emulsion with a sharp particle size distribution of droplets of the aqueous phase is obtained by this emulsification process, the particle size distribution of the spherical porous silica finally obtained is also sharp. When obtaining particles of preferably 1 μm or more and less than 100 μm, more preferably 8 μm or more and 90 μm or less, the rotation speed of the homogenizer is preferably 1,000 rpm or more and 15,000 rpm or less, more preferably 2,000 rpm or more and 12,000 rpm or less, and even more preferably 4,000 rpm or more and 9,000 rpm or less. The stirring time is preferably 30 seconds or more and 1 hour or less, more preferably 1 minute or more and 30 minutes or less.
[0049] (Gelling process) The gelation step is a step of gelling the fumed silica dispersion in a state where droplets of the fumed silica dispersion are dispersed in a non-aqueous solvent, following the W / O emulsion preparation step. The gelation can be carried out by a known method. For example, the gelation can be easily promoted by a method of heating to a high temperature or a method of adjusting the pH of the fumed silica dispersion to a weak acidic or basic state. The above-mentioned methods are preferable in that the reaction can be controlled independently. The pH of the fumed silica dispersion prepared by the above-mentioned method and not subjected to pH adjustment is generally in the range of 3.0 to 4.5.
[0050] When heating is performed, the temperature should not exceed the boiling point of each solvent used, and the lower limit of the gelation temperature is preferably 50° C., more preferably 60° C. The upper limit is preferably 100° C. or lower, more preferably 90° C. or lower.
[0051] The pH adjustment can be easily carried out by mixing a substance (called a "latent base") that exhibits basicity when thermally decomposed by heating, such as urea, with the fumed silica dispersion in advance, and then heating the mixture during gelation to increase the pH, or by adding a base to the emulsion while maintaining the W / O emulsion state by stirring the mixture with a mixer or the like.
[0052] Specific examples of the base include ammonia, tetraalkylammonium hydroxides such as tetramethylammonium hydroxide (TMAH), amines such as trimethylamine, alkali hydroxides such as sodium hydroxide, alkali metal carbonates such as sodium carbonate and sodium hydrogen carbonate, and alkali metal silicates. The intensity of the stirring may be strong enough to mix the W / O emulsion with the base.
[0053] Among the above pH adjustment methods, the method of thermal decomposition of latent base such as urea, or the method of using ammonia, tetraalkylammonium hydroxides, or amines as a base are preferred, since they are free of metal element contamination. When ammonia is used for pH adjustment, ammonia may be blown in as a gas or may be added as aqueous ammonia. It is particularly preferred to employ pH adjustment using urea, since it is possible to adjust the pH uniformly throughout by heating.
[0054] When adjusting the pH to promote gelation, it is particularly preferable to adjust the amount of addition so that the pH value of the fumed silica dispersion rises to about 4.5 to 8.0. The same applies to the case where a latent base is used, but for example, a specific amount of addition when urea is used is preferably 1% by mass or more, and particularly preferably 2% by mass or more, relative to the fumed silica dispersion. The upper limit is preferably 7% by mass or less, and more preferably 5% by mass or less.
[0055] When carrying out the above heating or pH adjustment, it is preferable to stir the gelled material in order to prevent the gelled material from agglomerating. A known method is generally used for stirring, and a specific example is a mixer equipped with stirring blades.
[0056] Furthermore, after gelation, the dispersoid changes from liquid to solid, so the system is no longer a W / O emulsion but becomes a dispersion (suspension) in which a solid (gelled body) is dispersed in a hydrophobic solvent.
[0057] (Gelated body recovery process) In this manufacturing method, the gelled body produced as described above is collected from the liquid. As a method for collecting the gelled body, a general solid-liquid separation method such as filtration or centrifugation can be used, but WO phase separation may be performed prior to the collection. WO phase separation is a process in which the gelled body dispersion is separated into two layers, an O phase and a W phase, and is generally also called demulsification. Here, the gelled body obtained by the gelling step is present on the separated W phase side. By separating this from the O phase, it becomes easier to collect the gelled body by solid-liquid separation such as filtration.
[0058] The WO phase separation method can be appropriately selected from known methods for demulsification, but is preferably performed by adding a certain amount of a water-soluble organic solvent that is usually used in demulsification to the gel dispersion and heating it to separate it into phases O and W. After this process, the upper layer generally becomes phase O (a layer mainly containing an organic solvent) and the lower layer becomes phase W (a water layer containing an aqueous organic solvent and a gel).
[0059] Examples of the water-soluble organic solvent include acetone, methanol, ethanol, isopropyl alcohol, etc. Among these, isopropyl alcohol is particularly suitable.
[0060] The amount of the water-soluble organic solvent added is preferably adjusted depending on the type and amount of the surfactant with an HLB value of 3 to 5 used during emulsion formation. For example, when sorbitan monooleate is used as the surfactant, the water-soluble organic solvent is added in an amount of about 1 / 6 to 1 / 2 times (water-soluble organic solvent / water-insoluble organic solvent) the mass of the water-soluble organic solvent, and the mixture is stirred as necessary and then allowed to stand, whereby demulsification can be suitably performed.
[0061] In WO phase separation, the surfactant migrates (extracts) to the O phase, so by removing the O phase, it is possible to obtain porous spherical silica that is free of impurities caused by the surfactant.
[0062] The heating temperature range is 50°C or higher, preferably about 50 to 80°C, and more preferably about 60 to 70°C.
[0063] After the water-soluble organic solvent is added to the gel dispersion as described above, it is preferable to stir the mixture to prevent the gel dispersion from agglomerating. A known method is generally used for stirring, and a specific example is a mixer equipped with a stirring blade. The degree of mixing is not particularly limited, but it is sufficient to rotate the liquid surface by stirring. For example, stirring with a mixer is performed at a speed of 0.1 to 3.0 kW / m 3 , preferably 0.5 to 1.5 kW / m 3 The stirring time is appropriately from 0.5 to 24 hours, and preferably from about 0.5 to 1 hour.
[0064] After the WO phase separation, the W phase containing the gel is recovered. Specifically, the O phase (upper layer) can be separated and removed by decantation or the like.
[0065] (drying process) The gelled material contained in the recovered W phase is preferably recovered from the W phase. A known method can be used for recovery, and specific examples include suction filtration and centrifugation. In this case, it is preferable that the solvent is removed so that the recovered gelled material is in the form of a cake.
[0066] The collected gel is dried by spray drying. When the gel is produced by a wet process as in the production method of the present invention, the capillary force of the solvent occurs between the particles of the gel when the gel is taken out of the liquid and dried. This causes the particles to aggregate, and especially when the particles are dried at rest, aggregation also occurs in the dried powder. On the other hand, by drying by spray drying, the droplet size of the solvent during drying can be made close to the particle size of the porous spherical silica particles. Ideally, if the droplet size of the solvent is equal to the particle size of the porous spherical silica particles, the droplet of the solvent during drying will contain one porous spherical silica particle at a time. In the above state, the porous spherical silica particles are not adjacent to each other during drying, so that the particles can be dried without the capillary force of the solvent occurring between them, and it is easy to obtain particles without aggregation. The spray drying method is not particularly limited, and known methods such as a rotary atomizer method and a nozzle method can be used, but it is preferable to select a method in which the particle size of the target porous spherical silica particles and the droplet size of the sprayed solvent are equal. In general, the nozzle type tends to produce finer droplets than the rotary atomizer type. The two-fluid nozzle type is particularly preferred from the viewpoint that the droplets can be made finer and are less likely to aggregate during drying.
[0067] The gelled body during spray drying is preferably dispersed in a water-soluble organic solvent in order to prevent aggregation. Specific examples of water-soluble organic solvents include acetone, methanol, ethanol, isopropyl alcohol, etc. By using a solvent with a lower boiling point, the drying efficiency can be improved.
[0068] The water-soluble organic solvent may be mixed with water or a non-water-soluble solvent. In order to suppress aggregation during drying, the concentration of the water-soluble organic solvent in the solvent is preferably 60% by mass or more, more preferably 65% by mass or more, and particularly preferably 70% by mass or more. If the concentration of the water-soluble organic solvent is within the above range, aggregation due to poor drying during spray drying is less likely to occur. In addition, since the drying shrinkage inside the pores can be adjusted by the concentration of the water-soluble solvent during drying, it is possible to cause moderate drying shrinkage and control the pore volume by adjusting the concentration of the water-soluble organic solvent. Specifically, by increasing the proportion of water contained in the solvent and decreasing the concentration of the water-soluble organic solvent, drying shrinkage is more likely to occur and the pore volume becomes smaller. Conversely, by reducing the proportion of water contained in the solvent and increasing the concentration of the water-soluble organic solvent, drying shrinkage is suppressed and the pore volume becomes higher.
[0069] The water-soluble organic solvent (slurry) in which the gel is dispersed is preferably stirred to prevent the particles from agglomerating in the liquid. A generally known method can be used for the stirring, and specific examples include a stirrer and a mixer with stirring blades. The degree of mixing may be such that the particles do not settle in the liquid and are not destroyed. The slurry may be charged into the spray dryer while being stirred, or may be charged into the spray dryer after being stirred for a certain period of time. From the viewpoint of preventing the particles from settling, it is more preferable to charge the slurry while being stirred.
[0070] The inlet temperature during spray drying is preferably adjusted to be equal to or higher than the boiling point of the solvent of the slurry, and the porous spherical silica is not in the form of a slurry or cake at the outlet of the spray dryer, but is a dry powder. The above-mentioned "equal to or higher than the boiling point" means equal to or higher than the boiling point of the solvent under pressure during drying. It is more preferable that the inlet temperature is adjusted to a value about 20 to 50°C higher than the boiling point of the solvent of the slurry, and the temperature difference between the inlet temperature and the outlet temperature is preferably adjusted to be in the range of 10 to 70°C. In general, a heater is set only at the inlet (inlet) of the spray dryer, and the outlet temperature does not exceed the inlet temperature. The temperature difference between the inlet temperature and the outlet temperature is more preferably in the range of 20 to 70°C, and particularly preferably in the range of 20 to 60°C. If the inlet temperature and the outlet temperature are within the above range, the drying state during spray drying is good, and porous spherical silica without aggregation is obtained.
[0071] The circulating air volume during spray drying may be adjusted so that the temperature inside the drying chamber is stable, and is preferably adjusted according to the scale of the spray dryer. When the dried porous spherical silica is collected using a cyclone, the circulating air volume affects the collection efficiency under the cyclone, and the larger the circulating air volume, the higher the collection efficiency under the cyclone.
[0072] The concentration of the gelled body contained in the slurry may be adjusted to such an extent that the slurry in which the gelled body is dispersed has fluidity and can be fed to a spray dryer without clogging. Specifically, the silica solids concentration (mass conversion) after drying is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less. There is no particular lower limit for the concentration of the gelled body, but since the lower the concentration, the lower the drying efficiency, it is preferable that it is not extremely low, and more preferably 5% by mass or more.
[0073] The slurry feed speed during spray drying may be adjusted so that the spray is stable and the inlet and outlet temperatures are the above-mentioned values, and is preferably adjusted according to the scale of the spray dryer. The slurry feed speed affects the temperature difference between the inlet and outlet temperatures, and the faster the feed speed, the larger the temperature difference between the inlet and outlet temperatures.
[0074] As a method for collecting the dried porous spherical silica, a generally known method can be used. Specifically, a one-point collection method, a two-point collection method, etc. can be mentioned. In addition, a general collector can be used, specifically, a cyclone, a bag filter, etc. From the viewpoint of removing coarse particles, it is preferable to collect by the two-point collection method using a cyclone.
[0075] (Firing process) The porous spherical silica of the present invention is further calcined after drying. Calcination can increase the test force at break. The calcination conditions may be adjusted so that the test force at break is the desired value, and the longer the calcination time and the higher the calcination temperature, the higher the test force at break. The calcination temperature is 900 to 1500°C. It is preferably 1400°C or less, and more preferably 1300°C or less. The calcination time is 10 to 25 hours. It is preferably 12 to 23 hours, and more preferably 12 to 20 hours. If the calcination temperature and calcination time are within the above ranges, the particles dried by spray drying without agglomeration do not agglomerate again, and the pores do not become clogged, and porous spherical silica having a test force at break in the desired range can be obtained.
[0076] As the firing method, a known method can be used. In general, the dried porous spherical silica is placed in a crucible or a quartz tray and heated in an electric furnace.
[0077] The atmosphere during firing is not particularly limited, and firing can be performed in an inert gas atmosphere such as argon or nitrogen, or in the air.
[0078] The heating rate during firing may be within a range that can be followed by the temperature rise of a heating device such as an electric furnace. Since the slower the heating rate, the lower the efficiency of the firing process, it is preferable that the heating rate is not too low. When using a general electric furnace, a heating rate of 2 to 10°C / min is suitable.
[0079] In the above manufacturing method, the particle size of the obtained porous spherical silica is almost the same as the droplet (W phase) diameter of the fumed silica dispersion in the W / O emulsion prepared in the emulsification step. Therefore, it is necessary to set the dispersion conditions so that the diameter is within the desired range. Various methods for controlling the droplet size in W / O emulsion are known, and these techniques may be appropriately selected and applied. As a method for adjusting the particle size of the droplets, a known method can be used, specifically, a method for adjusting the amount of surfactant added, or a method for adjusting the shear force applied during emulsification by the rotation speed, flow rate, etc. In the adjustment by the amount of surfactant added, the droplets tend to become finer when a large amount of surfactant is used, and the droplets tend to become larger when a small amount is used. In addition, in the adjustment by shear force, the droplets tend to become finer as the applied shear force increases, and the droplets tend to become larger as the applied shear force decreases.
[0080] The pore volume can be controlled by drying shrinkage. A known method for controlling drying shrinkage can be used, and specifically, a method of adjusting the concentration of the water-soluble solvent before drying can be mentioned. The pore volume can also be controlled by the firing conditions, and the higher the firing temperature and the longer the firing time, the smaller the pore volume. In addition, by using fumed silica as a raw material as in the manufacturing method of the present invention, the fumed silica has an aggregated structure, and the mode of the high pore radius is obtained. The specific surface area can be adjusted by appropriately selecting the specific surface area of the fumed silica used as a raw material, and can also be adjusted by the gelation time. The shorter the gelation time, the higher the specific surface area. The specific surface area can also be adjusted by the firing conditions. In general, the higher the firing temperature and the longer the firing time, the lower the specific surface area.
[0081] The alkali metal content can be easily reduced by using fumed silica that is substantially free of alkali metals as a raw material as described above, and other raw materials that are also substantially free of alkali metals, and by carrying out production while paying sufficient attention to avoid contamination (mixing in of impurities) by those skilled in the art. Furthermore, when aiming to reduce the alkali metal content, the cake may be washed with water, an organic solvent, or the like after solid-liquid separation and before drying. The number of fragmented particles can be reduced by suppressing particle aggregation during the manufacturing process and not carrying out a crushing step, as in the manufacturing method of the present invention. In addition, care must be taken throughout the manufacturing process not to apply excessive load to the particles so that they are not destroyed. EXAMPLES
[0082] EXAMPLES The present invention will be described in detail below with reference to examples, although the present invention is not limited to these examples.
[0083] <Evaluation method> The produced porous spherical silica was evaluated for the following items.
[0084] (Particle size distribution and cumulative diameter on a volume basis measured using a Coulter counter) 0.1g of porous spherical silica was added to 40ml of ion-exchanged water and dispersed for 30 minutes using an ultrasonic cleaner (BRANSON BRANSONIC1510J-DTH manufactured by BRANSON). The particle size distribution of the dispersion was measured using a Multisizer III manufactured by Beckman Coulter, Inc. An aperture with a diameter of 100μm was used for the measurement. From the obtained particle size distribution, the cumulative 50% diameter, cumulative 10% diameter, and cumulative 90% diameter on a volume basis were evaluated.
[0085] (Measurement of BJH pore volume, pore radius (mode) and BET specific surface area) The BJH pore volume, pore radius (mode value), and BET specific surface area were measured using a BELSORP-mini (manufactured by BEL Japan Co., Ltd.) according to the above-mentioned definitions.
[0086] (Test force at which specimen destruction is observed) The "test force at which the specimen was broken" was measured using a micro-compression tester (Shimadzu Corporation, MCT-W510-J) according to the above definition. The loading speed during the measurement was 0.4462 mN / sec, and the load holding time was 10 sec. An indenter with a diameter of 200 μm was used for the measurement.
[0087] (Alkali metal content) 10 ml of nitric acid and 10 ml of hydrofluoric acid were added to 1 g of porous spherical silica and dissolved. The solution was heated at 180°C for 4 hours and evaporated to dryness. After cooling to room temperature, 2 ml of nitric acid and 18 ml of ultrapure water were added and the total volume was increased to 20 ml to obtain a measurement sample. The alkali metal content of the obtained measurement sample was measured using an inductively coupled plasma emission spectrometer (Thermo Scientific, ICAP650DUO).
[0088] (Average circularity) For more than 2000 porous silica particles, SEM images were observed at 1000x magnification using a SEM (Hitachi High-Technologies S-5500, accelerating voltage 3.0 kV, secondary electron detection), and the average circularity was calculated according to the definition described above.
[0089] (Number of fragmented particles (number of particles with a circularity of 0.7 or less)) For more than 200 porous silica particles, SEM images were observed at a magnification of 800x using an SEM (Hitachi High-Technologies S-5500, accelerating voltage 3.0 kV, secondary electron detection) and image analysis was performed. The circularity of each particle was calculated according to the definition described above, and the number of particles with a circularity of 0.7 or less was counted.
[0090] <Example 1> (Dispersion liquid preparation process) To 200 ml of ion-exchanged water in which 6.65 g of urea was dissolved, 66 g of Reolosil QS-30 (manufactured by Tokuyama Corporation) was added while stirring with a homogenizer (manufactured by IKA, T25BS1), and the fumed silica was pre-dispersed, and then finely dispersed using an ultrasonic homogenizer (manufactured by BRANSON, Sonifier SFX250) to obtain a fumed silica dispersion. The particle size distribution of the dispersed liquid was measured by a laser diffraction scattering method, and the D90 value was 0.19 μm. The dispersion preparation process was carried out in a chiller cooled to 10°C.
[0091] (W / O emulsion preparation process) 65.5 g of the fumed silica dispersion prepared by the above method was taken, and 129 g of decane in which 0.75 g of sorbitan monooleate (Kao Corporation, Rheodol SP-010V) had been dispersed was added. The mixture was then stirred for 3 minutes at 8,600 rpm using a homogenizer to obtain a W / O emulsion.
[0092] (Gelling process) The obtained W / O emulsion was gelled by stirring at 200 rpm using a four-paddle impeller with a blade diameter of 60 mm, a blade width of 20 mm, and an oblique angle of 45 degrees while keeping it in a water bath at 80°C for 3 hours.
[0093] (Gelated body recovery process) 77 g of isopropyl alcohol and 52 g of water were added, and the mixture was stirred with a stirring blade while maintaining the temperature at 70° C. for 30 minutes. After that, the mixture was allowed to stand to separate into two layers, with the O phase as the upper layer and the W phase as the lower layer.
[0094] Then, the O phase and the W phase were separated by decantation, and the W phase was recovered.
[0095] The W phase was filtered by suction, and the gel was separated from the W phase by filtration.
[0096] (drying process) The gel cake obtained was dispersed in 60 g of isopropyl alcohol and, while stirring with a stirrer, was put into a spray dryer (BUCHI, Mini Spray Dryer B-290). At this time, the silica solid content in the slurry after drying was 10 mass%. The inlet temperature of the spray dryer was 120°C, and the outlet temperature was 85°C. The liquid delivery speed was 15 ml / min, and the circulating air volume was 35 m 3 / h.
[0097] (Firing process) The obtained dried powder was placed in a crucible and fired in an electric furnace (Advantec, FUS722PB) at 1000° C. for 20 hours with a heating rate of 5° C. / min. The firing atmosphere was not adjusted, and the firing was performed in an air atmosphere.
[0098] The physical properties of the porous spherical silica thus obtained are shown in Table 1. (The physical properties of the porous spherical silica obtained in the following Examples and Comparative Examples are also shown in Table 1.)
[0099] <Example 2> Porous spherical silica was obtained in the same manner as in Example 1, except that the firing conditions were changed to 900°C for 17 hours. The outlet temperature during spray drying was 85°C.
[0100] <Example 3> Porous spherical silica was obtained in the same manner as in Example 1, except that the rotation speed of the homogenizer in the W / O emulsion preparation step was changed to 3000 rpm. The outlet temperature during spray drying was 85°C.
[0101] <Example 4> Porous spherical silica was obtained in the same manner as in Example 1, except that the rotation speed of the homogenizer in the W / O emulsion preparation step was changed to 10,000 rpm. The outlet temperature during spray drying was 85°C.
[0102] <Example 5> Porous spherical silica was obtained in the same manner as in Example 1, except that the firing conditions were changed to 1200°C for 15 hours. The outlet temperature during spray drying was 85°C.
[0103] <Example 6> Porous spherical silica was obtained in the same manner as in Example 1, except that the rotation speed of the homogenizer in the W / O emulsion preparation step was changed to 6000 rpm and the firing conditions were changed to 1200°C for 10 hours. The outlet temperature during spray drying was 85°C.
[0104] <Comparative Example 1> 500mL of silica sol was prepared by adding 10g / 100mL of sulfuric acid to an aqueous sodium silicate solution with a molar ratio of SiO2 / Na2O of 3.1 so that the pH was 2.9. 66.5g of this silica sol was taken out, and the W / O emulsion preparation step, gelation step, and gelled body recovery step were carried out in the same manner as in Example 1, except that the fumed silica dispersion in Example 1 was changed to this silica sol, to obtain a gelled body. The obtained gelled body was dried in a vacuum dryer and fired at 1000°C for 20 hours to obtain porous spherical silica.
[0105] <Comparative Example 2> A fumed silica dispersion prepared in the same manner as in the dispersion preparation step of Example 1 was spray-dried and then calcined at 1000° C. for 20 hours to obtain porous spherical silica.
[0106] <Comparative Example 3> In Example 1, the rotation speed of the homogenizer in the W / O emulsion preparation step was changed to 5500 rpm, and the gelation step and gelled body recovery step were carried out to obtain a gelled body. The obtained gelled body was dried in a vacuum dryer and fired at 1000°C for 20 hours. After firing, the gelled body was crushed using a jet mill to obtain porous spherical silica.
[0107] <Comparative Example 4> Porous spherical silica was obtained in the same manner as in Example 1, except that the calcination step was not carried out.
[0108] <Comparative Example 5> Porous spherical silica was obtained in the same manner as in Example 6, except that the calcination was carried out at 800° C. for 10 hours.
[0109] [Table 1]
[0110] <Evaluation Results> (Examples 1 to 6) As shown in Table 1, in Examples 1 to 6, the arithmetic mean value of the "test force at which the specimen was broken" for 10 particles, calculated at a loading speed of 0.4462 mN / sec according to the method specified in JIS Z8844, was 1.0 × 10 1 ~2.0×10 1 The hardness was high, with a circularity of 0.7 or less, and the number of fragmented particles was reduced, with 20 or less particles having a circularity of 0.7 out of 200 particles observed in an SEM image. This can be achieved by drying the gel obtained by gelling the fumed silica dispersion in liquid by spray drying under appropriate drying conditions, as in the production method of the present invention, thereby suppressing particle aggregation, and then firing the gel under appropriate firing conditions.
[0111] In addition, all of the porous spherical silica obtained in Examples 1 to 6 had a D50 in the range of 2 to 200 μm, a D10 / D90 of 0.3 or more, a pore volume according to the BJH method in the range of 0.5 to 8 ml / g, a mode of the pore radius according to the BJH method in the range of 5 nm or more and 50 nm or less, and a specific surface area according to the BET method of 50 m 2 / g or more, 400m 2 / g or less, and the alkali metal content was 50 ppm or less.
[0112] In Examples 1 to 6, porous spherical silica with various D50 values was obtained, all of which were controlled by adjusting the droplet size of the W / O emulsion by changing the rotation speed during emulsification. The production method of the present invention makes it possible to easily control the D50 value of porous spherical silica without making major changes to the production process.
[0113] Comparative Example 1 The porous spherical silica of Comparative Example 1, which uses sodium silicate as a raw material, has a small pore volume. This is because the sodium from the raw material remains, causing a drop in melting point during firing, which causes the pores to become blocked. Thus, when sodium silicate is used as a raw material, it is difficult to obtain porous spherical silica with high hardness while maintaining the pore volume.
[0114] Comparative Example 2 The porous spherical silica of Comparative Example 2 obtained by spray drying the fumed silica dispersion had a low breaking test force. This is due to the low bond strength between the primary particles of the raw material before firing. Thus, when granulated by spray drying, it is difficult to obtain porous spherical silica with the desired hardness.
[0115] Comparative Example 3 The porous spherical silica of Comparative Example 3, which was recovered from the gel and then dried by standing in a vacuum dryer, had a large number of fragmentary particles. This is because the particles were aggregated during the standing drying, and fragmentary particles were generated by the crushing process. Thus, it is difficult to obtain porous spherical silica with a reduced number of fragmentary particles by standing drying.
[0116] Comparative Example 4 The porous spherical silica of Comparative Example 4, which was not subjected to the calcination step, had a low breaking test force. As described above, it is difficult to obtain porous spherical silica with high hardness without performing the calcination step.
[0117] Comparative Example 5 The porous spherical silica of Comparative Example 5 had a low breaking test force. As described above, unless the firing conditions are appropriate, it is difficult to obtain porous spherical silica with high hardness.
Claims
1. A volume-based cumulative 50% diameter (D50) measured by a Coulter counter method is in the range of 2 μm to 200 μm, Similarly, the ratio (D10 / D90) of the cumulative 10% diameter (D10) to the cumulative 90% diameter (D90) is 0.3 or more, The pore volume according to the BJH method is 0.5 ml / g or more and 8 ml / g or less, The most frequent pore radius measured by the BJH method is 5 nm or more and 50 nm or less, BET specific surface area is 50m 2 / g or more, 400m 2 / g or less, According to the method specified in JIS Z8844, the arithmetic mean value of the "test force at which the specimen was broken" for 10 particles was calculated at a loading rate of 0.4462 mN / sec and was 1.0 x 10 1 mN or more 2.0 x 10 1 mN or less, 1. A porous spherical silica having an alkali metal content of 50 ppm or less.
2. A catalyst support comprising the porous spherical silica according to claim 1.
3. A cosmetic comprising the porous spherical silica according to claim 1.
4. An analytical column comprising the porous spherical silica according to claim 1.
5. An abrasive comprising the porous spherical silica according to claim 1.
6. A resin composition comprising the porous spherical silica according to claim 1.
7. A step of preparing a W / O emulsion comprising an aqueous phase having fumed silica dispersed therein and an organic phase mainly comprising a non-aqueous solvent; a step of heating the emulsion to gel the aqueous phase and obtain a gelled dispersion; A step of recovering the resulting gelled body from the liquid; and calcining the obtained porous spherical silica at a temperature of 900 to 1500° C. for 10 to 25 hours; A method for producing porous spherical silica comprising the steps of:
Citation Information
Patent Citations
Ceramic particle and method of manufacturing the same
JP2010100503A
Production method of porous spherical metal oxide
JP2014210671A
Porous silica particles
JP2020193144A
Method for producing spherical silica powder
JP2022090679A
Porous silica particles and method for producing same
WO2019131873A1